2021
DOI: 10.1111/iju.14685
|View full text |Cite
|
Sign up to set email alerts
|

Does the microbiota spectrum of prostate secretion affect the clinical status of patients with chronic bacterial prostatitis?

Abstract: To explore the influence of the microbiota of prostate secretion on the clinical status of patients with chronic bacterial prostatitis. Methods: This was an observational, single-center, comparative study. We evaluated the survey cards of 230 outpatients aged 18-45 years with a history of prostatitis from 2012 to 2019. As a result, 170 outpatients were selected for the study. All patients underwent an assessment of symptoms using International Prostate Symptom Scorequality of life, National Institutes of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Comparison of the microbiota in the specimens between patients with CP/CPPS and controls differed in various urologic disorders, including CP/CPPS. Table 1 lists the previous studies addressing the possible association between CP/CPPS and the composition of the microbiota 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 . Choi et al.…”
Section: Cp and Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the microbiota in the specimens between patients with CP/CPPS and controls differed in various urologic disorders, including CP/CPPS. Table 1 lists the previous studies addressing the possible association between CP/CPPS and the composition of the microbiota 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 . Choi et al.…”
Section: Cp and Microbiomementioning
confidence: 99%
“… The main components that determine the severity of symptoms are an increase in microbial load and qualitative differences in the composition of the microbiota. 24 CP/CPPS, chronic prostatitis/chronic pelvic pain syndrome; CP, Chronic prostatitis. …”
Section: Cp and Microbiomementioning
confidence: 99%
“… Less microbial diversity could be associated with CP symptoms. Small sample Kogan et al (2021) 23 170 with CP/CPPS Post-massage urine (VB3) Meares–Stamey test In patients with CP/CPPS, a predominance of anaerobes or a combination of aerobes and anaerobes in a titer of >10 3 colony-forming units per mL in post-massage urine is associated with worse clinical status. Cluster analysis not done …”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 99%
“… 18 Although there are overlapping symptoms between CP/CPPS and bacterial prostatitis or sexually transmitted infections, the presence and type of bacteria on conventional culture did not correlate with the presence or severity of CP/CPPS. 19 Several studies have evaluated the diversity of microbiome in patients with CP/CPPS patients in comparison with that of controls 2 , 11 , 17 , 20 , 21 , 22 , 23 and found that bacterial species are increased in the urine or seminal fluids of patients with CP/CPPS, although definitive patterns are lacking. Elevations of multiple bacterial taxa including Clostridia and Bacteroidia 20 in urine and Achromobacter, Stenotrophomonas, and Brevibacillus 22 in seminal fluids have been identified in patients of CP/CPPS, whereas levels of Lactobacilli are decreased in patients with CP/CPPS.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 99%
“…The diversity of microbiota in the prostate of patients with CP/CPPS is significantly different to that of healthy people (Nickel et al, 2015;Shoskes et al, 2016). For example, Kogan et al (Kogan et al, 2021) reported that in patients with chronic bacterial prostatitis, a predominance of anaerobes or a combination of aerobes and anaerobes in a titer of ≥103 colony-forming units per mL in post-massage urine is associated with worse clinical status. At present, accumulating evidence confirm that depression is closely related with the health condition of the brain-gut axis, and maintaining/restoring the normal condition of gut microbiota helps in the prevention/therapy of mental disorders.…”
Section: Introductionmentioning
confidence: 99%